ANALISIS POTENSI DAYA DUKUNG LAHAN UNTUK PENGEMBANGAN SAPI POTONG DI KAWASAN PAKAKAAN KABUPATEN MINAHASA - Tiwow, H. A.L; Panelewen, V. V.J; Mirah, Arie Dp. (ZOOTEC, 2016)
ANALYSIS OF LAND CARRYING CAPACITY AND ITS POTENCY FOR BEEF CATTLE DEVELOPMENT IN PAKAKAAN MINAHASA REGENCY. This study has been conducted in The PAKAKAAN, Minahasa Regency on February 2nd - April 5th 2014. The study aimed to: identify and calculate the carrying capacity of the land as a source of forage feed. Method of analysis that used in this study was descriptive analysis, where the research locations was selected by purposive sampling method, with consideration that the area is agropolitan region, in which beef cattle as the main commodity. Data collected were included secondary data. Secondary data were from: a) Minahasa Statistics Center Bureau, b) the Department of Agriculture, Livestock and Agriculture Service of Minahasa, c) reading material and results of research published by official agencies. The source of the data that is; a) the stakeholders (farmers / ranchers, merchants, butcher, retailers and consumers of beef) b) experts / specialists (college / Toma) c) SKPD and related agency in Minahasa. The data was then processed and analyzed through the calculation land capacity index. Pakakaan is a region defined by the government Minahasa as an Agropolitan region where its main commodity is beef cattle. This region has an area extent of about ​​356.68 km2, which spread in 10 sub-districts. By 2013 the population in the region were 106.270 inhabitants, the population density per districts amounted to an average 298 people/km2 (Department of Agriculture and Minahasan Livestock and Agriculture Service, 2014). The land area extent in the region was 32.010 hectares, with the total number of agricultural households (HH) were 27.264, the density was 1.77 ha/HH. Cattle population in the year 2013 as many as 10.581 heads, thenumber of cattle farmers were 4.038, which means the averageof cattle ownership was 2.62 heads/farmer, and the beef cattle density was 29.67 heads/km2. The results showed that with a land area of ​​32.010 hectares will be able to produce forage for cattle in the amount of 11.541 tonnes per year, while the roughage can be generated by 123.934 tonnes per year. These means that the average of feed potential availability as much as 135.484 tonnes per year. Based on the livestock unit analysis, the animal unit (AU)of cattle population was 8.040 AU, in which the total capacity of cattle was 118.846AU/year, when it subtracted by the recent  total cattle population there, hence the development potential was 108.740 AU per year. It is concluded:1)the land carrying capacity index (CCI) for the development of beef cattle in the Pakakaan region was in the category of "safe" with a value of>2,   Keywords : beef cattle, animal unit, capability index.